Cognitive reflection and the disposition effect: a lab experiment - Newton da Costa Jr.; André Grezelle; Marco Goulart; H. K. Pradhan (Privietlab, 2023)
This research investigates the connection between cognitive reflection and the disposition effect, a well-known bias in the behavioral finance literature. Utilizing the Cognitive Reflection Test (CRT) developed by Frederick (2005), we measured cognitive abilities in a laboratory-based experiment comprising 55 students. The main goal was to investigate the extent to which these cognitive resources might modulate the disposition effect. The study was conceptualized within the framework of the dichotomy between a deliberative long-term self and an impulsive short-term self, as detailed in Kahneman's 2011 two-systems theory. The findings indicate a significant negative correlation between cognitive abilities and the disposition effect, providing extra empirical support for Kahneman's theory. This study presents new empirical evidence of the association between cognitive reflection and behavioral biases associated with decision-making under conditions of risky, thus providing a basis for possible interventions to mitigate these biases. The implications of this study are not limited to academia, but may provide information for the development of future financial education programs to enhance the decision-making process of individuals, whether in public or private companies.